The Implementation of the Reflective Inquiry Learning Model to Improve Students’ Metacognitive Skills in Informatics Subject at State Senior High School 1 Amurang - Wagei, Suci K.; Manggopa, Hiskia Kamang; Angmalisang, Harrychoon; Rompas, Parabelem Tinno Dolf (International Journal of Information Technology and Education, 2026)
Metacognitive skills are an essential aspect of Informatics learning, as they are closely related to students’ ability to plan, monitor, and evaluate their own thinking processes. However, learning outcomes indicate that students’ metacognitive skills remain relatively low. This study aims to improve students’ metacognitive skills through the implementation of the Reflective Inquiry learning model. This study employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 33 eleventh-grade students at SMA Negeri 1 Amurang. Research instruments included a metacognitive questionnaire, observation sheets of teacher and student activities, and learning achievement tests. The results showed an improvement in students’ metacognitive skills from Cycle I to Cycle II, as indicated by an increase in the average metacognitive score and the percentage of students categorized as having high metacognitive skills. Therefore, the Reflective Inquiry learning model is effective in improving students’ metacognitive skills in Informatics learning.